Análisis de riesgos crediticios para la Cooperativa de Ahorro y Crédito 9 de octubre ltda., cantón Salcedo, provincia del Cotopaxi, período 2014 - Andrade Villalva, Estefanía Jazmina (2016)
In this thesis it has been to consider a credit risk analysis; first, it will make an assessment of the financial statements of the cooperative through indicators and conducting analysis to account portfolio as an object of study. One common measure of financial institutions are the approval of loans for customers, both individual corporate. These credits can be in the form of loans or lines of credit (like credit cards) and other products. The financial institution assumes the risk that the debtor fails to play its debt and agreed interest. Thanks to the applied ethos such as interviews and survey, has obtained key information about the object of study, and being that the credit risk exist mainly by two factor, one to the activity itself; and the other by the inefficient and inadequate implementation of credit policies….